AN ANALYSIS OF CODE SWITCHING IN THE NOVEL 9 SUMMERS 10 AUTUMNS - Wenny Yuliani (English Department, Faculty of Humanities, Andalas University, 2013)
This study is aimed to describe the types and the functions of code switching which are uttered by the characters in the novel 9 Summers 10 Autumns. In collecting the data, non participatory observational method (Sudaryanto 1993) was applied. In analyzing the data, Hoffman’s theory (1996) is referred to analyze the types of code switching and Gumperz’s theory (1982) is referred to analyze the functions of the code switching. Presenting the result of analysisis is done formally and informally. After analyzing the data, the writer finds three types of code switching. They are inter-sentential switching (fifteen times), intra-sentential switching (four times), and emblematic switching (twice). Meanwhile, there are four functions of the code switching; message qualification, addressee specification, interjection and personalization. It means, there are two functions that do not appear in the data; quotation and reiteration, because the characters never quote other people’s ideas or repeat utterances from other language. Keywords: code switching, types of code switching, functions of code switching